2005
DOI: 10.1159/000084792
|View full text |Cite
|
Sign up to set email alerts
|

Is There an Association between Low Birth Weight and Caries in the Primary Dentition?

Abstract: Objectives: An association between low birth weight and caries in the primary dentition has been suggested but not demonstrated. This study analyzed this association using data from a probability sample of US children 2–6 years of age. Methods: Data from the Third National Health and Nutrition Examination Survey (NHANES III) were used. Variables included decayed and filled primary surfaces (dfs), birth weight, gestational age, and Apgar score (a surrogate measure of fetal well-being); maternal age, education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
92
2
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(111 citation statements)
references
References 34 publications
9
92
2
7
Order By: Relevance
“…However, their results relating to the correlation between DMFT and preterm birth were similar to previous findings, showing no associations (9). On the other hand, Shulman (20) did not find any association between low birth weight and caries.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, their results relating to the correlation between DMFT and preterm birth were similar to previous findings, showing no associations (9). On the other hand, Shulman (20) did not find any association between low birth weight and caries.…”
Section: Discussionsupporting
confidence: 76%
“…A less smooth, less mineralized enamel might be more prone to caries (7,15). Nevertheless, this study as well as some others, showed that these items were not correlated (12,14,15,19,20).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Alguns estudos verificaram que crianças com baixo peso ou desnutridas apresentam maior prevalência de cárie dentária 6,15 . Entretanto, outros estudos que avaliaram a associação entre o número de dentes cariados e o estado nutricional infantil não encontraram associação significativa 12,16,17 assim como no presente estudo. A ausência de associação pode ter ocorrido pela maior prevalência de alterações no estado nutricional em crianças mais novas que apresentam menor prevalência de cárie dentária.…”
Section: Metodologia Resultadosunclassified